Secondary Resource Management Issues in Republic of Armenia - Detloff, Maro (ՀՀ ԳԱԱ)
The article is devoted to the need for effective management of secondary resources, the identification of existing problems in the Republic of Armenia and ways to solve them. The article analyzes the leading experience of developed countries in waste management, the current state of household solid waste (general type, paper, plastic, glass and biodegradable - bio) management according to the five-level 5R hierarchy of waste regulation. Հոդվածը նվիրված է երկրորդային ռեսուրսների արդյունավետ կառավարման անհրաժեշտությանը, Հայաստանի Հանրապետությունում առկա հիմնախնդիրների և դրանց լուծման ուղիների բացահայտմանը: Статья посвящена необходимости эффективного управления вторичными ресурсами, выявлению существующих проблем в Республике Армения и путям их решения.
Keywords: Social and Humanitarian Sciences